Hibah Komersial: Satu Tinjauan Terhadap Prosedur Dan Amalan Di Malaysia - Azhar, Alias Bin; Hussain, Mohammad Azam; Badarulzaman, Muhammad Hafiz; Mohd Noor, Fauziah (Universiti Sains Islam Malaysia, 2024)
Gifts (hibah) in accordance with Islam generally is one act of giving possession of the property to others without replacement. Therefore, a more systematic application Gifts (hibah) and commercial use today . Existing agencies are actively involved in the implementation of the Gifts . Trust Gifts (hibah amanah) is one method that is characterized by the integration of Gifts (hibah) and Trust (amanah). In fact and reality of Gifts (hibah) in Malaysia is involved documents and Pre-Gifts (hibah). Gifts Documentation a special procedure to encouraged the gift giver to do during his lifetime . Amanah Raya Berhad or AmanahRaya , formerly known as the Department of Public Trustee and Official Administrator was established on May 1, 1921 . It was incorporated on August 1, 1995 under the Companies Act 1965. AmanahRaya is a wholly owned government company with a market share of 99.99 % by the Minister of Finance (Incorporated ) and 0.01% by the Federal Land Commissioner . In addition, there are also some companies like Wasiyyah Shoppe , As- Salihin Trustee Bhd and Warisan Mukmin Sdn Bhd. is also listed in the category of companies operating actively in the planning and management especially Gifts (hibah). There are also companies that offer directly to the home services like www.wasiat4U.com . Roughly, there are many companies in Malaysia engaged in commercial activity in general estate management service oriented and Gifts (hibah) in particular . This paper explores aspects of the implementation and the procedures adopted in the form of Gifts (hibah) commercial product offering.